COVID‐19 in pregnancy: Placental and neonatal involvement. (15th August 2020) - Prochaska, Erica; Jang, Minyoung; Burd, Irina
Abstract: Since December 2019, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has caused over 12 million infections and more than 550 000 deaths. 1 Morbidity and mortality appear partly due to host inflammatory response. 2 Despite rapid, global research, the effect of SARS‐CoV‐2 on the developing fetus remains unclear. Case reports indicate that vertical transmission is uncommon; however, there is evidence that placental and fetal infection can occur. 3‐7 Placentas from infected patients show inflammatory, thrombotic, and vascular changes that have been found in other inflammatory conditions. 8, 9 This suggests that the inflammatory nature of SARS‐CoV‐2 infection during pregnancy could cause adverse obstetric and neonatal events. Exposure to intrauterine inflammation and placental changes could also potentially result in long‐term, multisystemic defects in exposed infants. This review will summarize the known literature on the placenta in SARS‐CoV‐2 infection, evidence of vertical transmission, and possible outcomes of prenatal exposure to the virus.